2015
DOI: 10.1186/1471-2164-16-s8-s1
|View full text |Cite
|
Sign up to set email alerts
|

Better prediction of functional effects for sequence variants

Abstract: Elucidating the effects of naturally occurring genetic variation is one of the major challenges for personalized health and personalized medicine. Here, we introduce SNAP2, a novel neural network based classifier that improves over the state-of-the-art in distinguishing between effect and neutral variants. Our method's improved performance results from screening many potentially relevant protein features and from refining our development data sets. Cross-validated on >100k experimentally annotated variants, SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
447
5
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 544 publications
(493 citation statements)
references
References 56 publications
8
447
5
2
Order By: Relevance
“…For this purpose, different bioinformatics tools were used: PolyPhen-2 (Adzhubei et al, 2010), SIFT (Kumar et al, 2009), Mutation Taster (Schwarz et al, 2014), MutPred (Li et al, 2009), and SNAP 2 (Hecht et al, 2015). The following NCBI reference sequences were used: NG_007370.1 (gene), NM_139,276.2 (mRNA) and NP_40,763.1 (protein).…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, different bioinformatics tools were used: PolyPhen-2 (Adzhubei et al, 2010), SIFT (Kumar et al, 2009), Mutation Taster (Schwarz et al, 2014), MutPred (Li et al, 2009), and SNAP 2 (Hecht et al, 2015). The following NCBI reference sequences were used: NG_007370.1 (gene), NM_139,276.2 (mRNA) and NP_40,763.1 (protein).…”
Section: Methodsmentioning
confidence: 99%
“…SIFT (http://sift.jcvi.org/) [34], Provean (http://provean.jcvi.org) [35] and SNAP (https://rostlab.org/services/snap/) [36] algorithms were used to determine the functional effect of non-synonymous SNPs.…”
Section: Analysis Of the Variants In The Salt Tolerance Related Genesmentioning
confidence: 99%
“…In general, many different machinelearning models perform equally well; for example, the latest version of SNAP averages .10 different predictors with similar performance, for which evolutionary conservation is the only feature in common to all 10 (Hecht et al 2015). The advantage of machine-learning approaches is that they can include features of very different types, and potentially a large number of such features that can be combined in highly complex and nonlinear ways.…”
Section: Combining Sequence Conservation With Structural Featuresmentioning
confidence: 99%
“…For example, for SNPs&GO (Capriotti et al 2013b) the same learning procedure was followed with and without the additional Gene Ontology information (Ashburner et al 2000) to quantitate the improvement in prediction accuracy from this one additional data source. SNAP2 (Hecht et al 2015) reported results for multiple different machine-learning methods using the same set of features. The FATHMM article (Shihab et al 2013) reported the performance of their method before and after incorporating protein domain-specific pathogenicity weights.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%